Atherogenic index of plasma as a stroke-subtype–independent predictor of acute cognitive dysfunction in ischemic stroke: A cross-sectional analytic study - Christian Haurissa, David; Amran, Muhammad Yunus; Akbar, Muhammad; Muis, Abdul; Goysal, Yudy; Alfian Zainuddin, Andi (Acta Biomedica Atenei Parmensis, 2026)
Background and aim: Cognitive impairment is a common complication in the acute phase of ischaemic stroke (IS). The Atherogenic Index of Plasma (AIP) has been proposed as a potential marker of vascular risk; however, its relationship with cognitive function across different stroke subtypes remains unclear. This study aimed to evaluate the association between AIP and cognitive performance, with consideration of IS subtypes, using the Montreal Cognitive Assessment Indonesian Version (MoCA-Ina). Methods: A cross-sectional analytic study was conducted at Dr. Wahidin Sudirohusodo General Hospital, Makassar, from July to December 2025. Patients aged ≥40 years with first-ever acute ischaemic stroke (onset 24 hours–7 days) and preserved consciousness were included. Exclusion criteria comprised recurrent stroke, transient ischaemic attack, aphasia, pre-existing dementia, systemic or psychiatric conditions affecting cognition or lipid metabolism, and prior lipid-lowering therapy. AIP was calculated as log₁₀ (triglyceride/HDL-C). Cognitive function was assessed using MoCA-Ina, and stroke subtype was classified as lacunar or non-lacunar. Statistical analyses included Spearman correlation, Mann–Whitney, and independent t-tests. Results: Most patients showed cognitive impairment (74%; median MoCA-Ina 23.00) and high-risk AIP levels (65%; mean 0.285). AIP demonstrated a significant negative correlation with total MoCA-Ina score (r = -0.342; p = 0.001). Non-lacunar stroke patients showed lower cognitive scores compared with lacunar stroke (mean 19.02 vs 21.90; p = 0.028). In contrast, AIP values did not differ between subtypes (p = 0.991). Conclusions: Higher AIP is associated with worse cognitive performance in the acute phase of ischaemic stroke. This finding suggests that atherogenic dyslipidaemia may contribute to early cognitive decline irrespective of stroke subtype.